2004
DOI: 10.1063/1.1649680
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Quantum Source of High-Frequency Gravitational Waves (HFGW) and Test Methodology

Abstract: Abstract. The generation of High-Frequency Gravitational Waves (HFGW) has been identified as the required breakthrough that will lead to new forms of space propulsion. Many techniques have been devised to generate HFGW, but most of them exhibit marginal efficiency, therefore the power emitted in form of gravitational waves (GW) is orders of magnitude lower than the input power. The gravitational wave counterpart of the LASER, termed Gravitational-wave LASER or "GASER" is the quantum approach to the efficient g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Refractive properties, which lead to the concept of HFGW optical systems, were first published by Ning Li and David G. Torr, in 1992 in which on p. 5491 they demonstrated that the phase velocity of a GW, ν p , was reduced by a factor of about 300 in a superconductor (actually, about a factor, termed the index of refraction, N, of 400±200). This paper was peer reviewed and examined by C. A. Lundqist and Jeeva Anandan, but their results are disputed by Kowitt (1994. Fontana (2004, however, suggests that there is some change in the phase velocity in a SC and an attendant increase in the index of refraction, N. Thus we will keep the question open.…”
Section: X-ray Laser Hfgw Generator For Experimentsmentioning
confidence: 99%
“…Refractive properties, which lead to the concept of HFGW optical systems, were first published by Ning Li and David G. Torr, in 1992 in which on p. 5491 they demonstrated that the phase velocity of a GW, ν p , was reduced by a factor of about 300 in a superconductor (actually, about a factor, termed the index of refraction, N, of 400±200). This paper was peer reviewed and examined by C. A. Lundqist and Jeeva Anandan, but their results are disputed by Kowitt (1994. Fontana (2004, however, suggests that there is some change in the phase velocity in a SC and an attendant increase in the index of refraction, N. Thus we will keep the question open.…”
Section: X-ray Laser Hfgw Generator For Experimentsmentioning
confidence: 99%
“…Frequency modulation of a particle wavefunction (by vibrations at relativistic speeds in the 3-space) should change its frequency spectrum and control the intensity of natural forces. Experiments very similar to those devised for studying High Frequency Gravitational Waves (HFGW) (Fontana, 2004 and2003b;Baker, 2004) are suggested to study the properties of the refractive index of the 4-space.…”
Section: Particles Forces and Gravitation In The 4-spacementioning
confidence: 99%
“…As suggested by Fontana (2004): "A large literature exists on colliding gravitational waves (Szekeres, 1972). It has been found that the collision or focusing Griffiths, 1995 and1996) of gravitational waves produce curvature singularities.…”
Section: Figurementioning
confidence: 99%
“…None of these effects utilized for detection represent interaction with matter, but with fields and do not attenuate the GWs. There are a number of alternative devices theorized to generate HFGWs in the laboratory such as the Russians: Grishchuk and Sazhin (1974), Braginsky and Rudenko (1978), Rudenko (2003), Kolosnitsyn and Rudenko (2007); the Germans: Romero and Dehnen (1981) and Dehnen and Romero-Borja (2003); the Italians: Pinto and Rotoli (1988), Fontana (2004); Fontana and Baker (2006); the Chinese: Baker, Li and Li (2006). The HFGW generation device or transmitter alternative selected is based upon bands of piezoelectriccrystal, film-bulk acoustic resonators or FBARs (Baker, Woods and Li, 2006) since they are readily available "off the shelf."…”
Section: Introductionmentioning
confidence: 99%